The effects of breeding systems and stocking density on some blood parameters of rock partridges (Alectoris graeca) - Ozbey, O.; Esen, F. (Poultry Science Assoc Inc, 2007)
In this study, the effects of breeding systems and stocking density on some blood parameters of rock partridges [total protein, total cholesterol, triglyceride, urea, glucose, calcium, phosphorus, alkaline phosphatase (ALP), sodium, chlorine, potassium, aspartate amino transferase (AST), and alanine amino transferase (ALT)] were investigated. For this purpose, blood samples of 18-wk-old male rock partridges, which were bred on the ground and in cages with 3 different stocking densities (group I: 15 partridges/m(2); group II: 20 partridges/m(2); and group III: 25 partridges/m(2)) were examined. Breeding method of rock partridges was found to have significant effects on blood total protein, (P < 0.05), total cholesterol (P < 0.05), triglyceride (P < 0.01), urea (P < 0.01), glucose (P < 0.05), calcium (P < 0.05), phosphorus (P < 0.01), ALP (P < 0.05), sodium (P < 0.01), chlorine (P < 0.05), and potassium (P < 0.01) levels, whereas it was found to have no significant effect on blood AST and ALT levels (P > 0.05). Stocking density of rock partridges was also found to affect significantly the levels of blood total protein, total cholesterol, triglyceride, urea, glucose, calcium, phosphorus, ALP, sodium, chlorine, and potassium (P < 0.05), whereas it did not have a significant effect on blood AST and ALT levels (P > 0.05). When the breeding method of the partridges was changed from the ground to the cages and the stocking density was increased, it was observed that the levels of blood total cholesterol, triglyceride, urea, glucose, sodium, and chlorine increased, whereas total protein, calcium, phosphorus, ALP, and potassium levels decreased. It was understood that the reactions of partridges toward breeding systems and stocking density were different and passing from ground system to cage system, and the increase in stocking density caused significant changes in blood parameters.
Keywords: rock partridge; breeding method; stocking density; blood parameter